Opportunities for Circular Initiatives via Waste Recovery in the Region of Campos Gerais, Brazil - Suarez, Franco Sebastián; Ortolani, Juan Martín; Barros, Murillo Vetroni; Salvador, Rodrigo; Araújo, Cristiane Karyn de Carvalho [UNESP]; Puglieri, Fabio Neves; Tesser, Daniel Poletto (Springer Nature, 2022)
Circular economy (CE) has been bringing innovative solutions to environmental problems without disregarding economic concerns, and one of the strategies to seek a more circular economy is industrial symbiosis. The objective of this chapter is to analyze the possibilities for waste recovery, from the exchange of waste and/or by-products, focusing on solid wastes, in the Campos Gerais region (Parana state, Brazil). To this end, wastes from a group of companies in the Campos Gerais region were studied. Twenty-five types of waste were identified, from which seven were hazardous and eighteen were nonhazardous. Nonhazardous wastes were classified into groups, and strategies for value recovery via industrial symbiosis were identified for each group. The greatest volume of the waste could be used for civil construction, energy recovery, and composting ends, whereas the greatest number of companies that could potentially make use of these wastes were from the civil construction, manufacturing of wood products, and food production sectors. Therefore, an imbalance in the supply and demand in a potential exchange of products can be seen. This calls for innovative solutions on the use of waste to fulfill local needs and take advantage of circular initiatives.
Keywords: Circular economy; Industrial symbiosis; Sustainability; Waste